SIKAP PETANI TERHADAP MEDIA PENYULUHAN DI DESA PENDEM KECAMATAN JUNREJO KOTA BATU - Farah Mutiara; A. Yusuf Kholil; Aleksius Satot (OPTIMA, 2022)
This research aims to find out the attitude of farmers towards counseling media in Pendem Village, Junrejo District, Batu City. The data collection methods used are observation, questionnaires, interviews and documentation. The data analysis technique used is descriptive analysis. Descriptive analysis is used to measure farmers' attitudes towards the extension media used. The decryption is done using a simple tabulation analysis tool and average score, then converted to a range of likert scales. The results stated that the extension media used by extensionists is a simple medium that is a direct contact media with the help of whiteboards and handouts containing data related to technical cultivation, so that it can be easily understood by farmers. The attitude of farmers towards counseling media in the research area can accept, respond to and appreciate the extension media used by PPL to convey extension materials, but farmers still cannot be responsible for the extension media used in the delivery of extension materials.Keywords: Attitudes of farmers and the Media counseling